Diversity of phythophythora spp. causing black pod rot on cocoa in Jasin district Melaka / Siti Nur Svazana Zakaria and Hamzah Abd Aziz - Zakaria, Siti Nur Svazana; Abd Aziz, Hamzah (Faculty of Plantation and Agrotechnology, 2018)
Cocoa was classified as economical crop in Malaysia agriculture industry. In early 2000. cocoa industry in Malaysia have declined in the number of production due to heavy infestation of pests and diseases. The most serious damage was caused by black pod rot. The major causal agents were first identify as Phvthoph\thora palmivora and Phythophvthora capsici which were commonly found in Peninsular Malaysia and Sabah. Phyhtophythora spp. have a large diversity and cocoa are suitable to be their host. In high-rainfall areas, increased soil moisture can increase the potential for black pod rot disease development. Melaka state has been reported the first cacao planted area in Malaysia which suitable to carried out research study on Phythophythora spp. diversity infected cacao. The isolates of Phythophythora spp. were grown on 3 media which were tomato juice agar (TJA). corn meal agar (CMA) and potato dextrose agar (PDA) to measure the growth responds. Koch's postulates was used to confirm the pathogenicity potential for all 6 species found. All isolates show positive results for pathogenicity' test in attacked healthy cocoa pod. The identification for all isolates were done based on a previous study on classification of Phythophythora. The Phytho-phvthora spp. that attack cacao pod in Jasin district have produce almost similar symptom development but different in the rate of infestions.